PRINSIP TAUHID DALAM DEMOKRASI ISLAM (SUATU ANALISIS PERSPEKTIF TEORI KEDAULATAN) - Muhaemin Muhaemin (Qaumiyyah: Jurnal Hukum Tata Negara, 2021)
The formulation of the principles of democracy in Islam has actually been compiled by many thinkers, both from insiders and outsiders. Of the many principles that exist, the author is interested in studying the principle of monotheism. This is because, this principle is the most essential principle in democracy from an Islamic perspective. This principle is then examined by the author based on the theory of sovereignty. The results of the author's study show that the principle of monotheism as part of the democratic principle in Islam is very much in line with the theory of sovereignty which wants a sovereign person who has power, as well as rules that are continuity and obedience. Abstrak Rumusan prinsip-prinsip demokrasi dalam Islam sebenarnya telah banyak disusun oleh para pemikir, baik dari dalam maupun dari luar. Dari sekian banyak asas yang ada, penulis tertarik untuk mengkaji asas tauhid. Sebab, asas ini merupakan asas yang paling esensial dalam demokrasi dari perspektif Islam. Prinsip ini kemudian dikaji oleh penulis berdasarkan teori kedaulatan. Hasil kajian penulis menunjukkan bahwa prinsip tauhid sebagai bagian dari prinsip demokrasi dalam Islam sangat sejalan dengan teori kedaulatan yang menginginkan pribadi yang berdaulat yang memiliki kekuasaan, serta aturan-aturan yang bersifat kontinuitas dan ketaatan.